ANALISIS PENDAPATAN DAN EFISIENSI PEMASARAN CABAI MERAH (Capsicum annuum L.) DI KECAMATAN WATANGPULU KABUPATEN SIDRAP - Rasidin, Rasidin; Yusriadi, Yusriadi; Rahman, Rahman (Universitas Negeri Makassar, 2018)
Most problems faced by farmers in red chili farming were production and price fluctuations that determines farmer`s income. This research aimed to assess the income and the marketing efficiency of red chili. The research locations were determined by purposive in Cirociroe village, Watangpulu Sub district. Respondents of this research were 20 red chili farmers that used by census method. The data of this research was collected on May – July 2018. The data analysis that were used in this research were descriptive and quantitative analysis. The income of red chili farmers was analyzed by R/C ratio. The marketing efficiency of red chili was analyzed by market structure, market conduct, and market performance. The results showed that red chili farming in Watampulu Sub district was profitable with the income of red chili farming was Rp46,336,000/ha. With 9.48 for R/C ratio and Efficiency 4.87% as value of marketing efficiency, so the marketing of red chili in Watangpulu Sub District-Sidrap Regency was efficient.